Anatomy and Utilization of two Cane Species of Kerala - Mohan Varghese (College of Forestry, 1988)
Variation in certain anatomical and physical properties has been investigated and compared in two rattan species, viz. Calamus thwaitesii and C. travancoricus, the former representing the larger diameter and the latter possessing small-diameter canes of kerala. Five stems possing more or less similar number of internodes have been sampled in each of two species. There were significant differences between the two species in certain physical properties such as length and diameter of internode, stem “wood” density and initial moisture content although volumetric shrinkage did not differ appreciably. Similarly, quantitative data for anatomical properties such as corted percentage, number of vascular bundles per unit area, vascular bundle diameter, xylem and phloem percentage, metaxylem vessel element and fibre dimensions were markedly different between the two species while the fibre percentage had almost similar values. With the exceptions of internode size and fibre width, the mean physical and anatomical properties in each species showed definite patterns of longitudinal variation, which could be best explained using quadratic regression models. However, patterns of longitudinal variation were different between the species in volumetric shrinkage, number of vascular bundles per mm2, vascular bundle diameter, phloem percentage, metaxylem vessel element and fibre length. The most important useful features in distinguishing between the two species are internode length, stem diameter, epidermal cell and its lumen shape, diameter and frequency of vascular bundles as well as the diameter of wide metaxylem vessels. The most important determining factors of “wood” density are fibre percentage, fibre wall thickness and lumen width as well as the diameter of metaxylem vessels although features like the size and number of vascular bundles per unit area also influences this property. Volumetric shrinkage and moisture content are inversely related to the density of “wood”. With higher density owing to more thick walled fibres and narrower wide metaxylem vessels, basal portion of the stem is harder and heavier than top portion.